An examination of the Neutral Penetration Model 1/ne, ped scaling for its validity of spatially varying neutral sources. (September 2021) - Simpson, J.; Moulton, D.; Giroud, C.; Casson, F.; Groth, M.; Chankin, A.; Horvath, L.; Gahle, D.S.; Garzotti, L.; Corrigan, G.; Kochl, F.
Highlights: EDGE2D-EIRENE simulations showed the dominant neutral source at the separatrix originates from the inner target for this specific JET H-mode plasma JETTO-EIRENE simulations were run with fixed transport and temperature profiles investigating the role of poloidal location of the neutral source. The 1 / n e, ped scaling from the Neutral Penetration Model is observed when fueling at the OMP but not at the X-point when measuring the density profile at the OMP. When measuring the density profile at the X-point and fueling at the X-point the 1 / n e, ped scaling is observed. Potentially this could experimentally verified if measured density profiles were remapped to a coordinate along the X-point, assuming that all neutral source enters at the X-point and the ionisation sets the density profile. Abstract: The core transport code, JETTO, coupled to the neutral Monte Carlo code, EIRENE, has been used to examine the sensitivity of the JET H-mode pedestal to the neutral flux crossing the separatrix. The Neutral Penetration Model (NPM) [Groebner et. al., Physics of Plasmas 9, 2134 (2002)] predicts the width of the density pedestal along the neutral path to scale with the inverse of its height: 1 / n e, ped . By keeping the same physics assumptions in the NPM, and setting the deuterium atoms to cross the separatrix at the same location as the synthetic diagnostic line of sight (i.e. at the outer mid-plane, OMP), we were able to reproduce this scaling in JETTO-EIRENE. However, when the atoms were set to cross the separatrix at the X-point (more consistent with EDGE2D-EIRENE simulations of JET H-modes), the density width at the OMP was found to be much more sensitive to the pedestal height (approximately proportional to 1 / n e, ped 2 ). This is attributed to a radial variation in the poloidal flux expansion from OMP to X-point, over the range of ionisation mean free path lengths explored in the scan. Accounting for this variation allowed the expected scaling at the OMP to be recovered. Implications are discussed for experimental comparisons to the NPM and its application to pedestal prediction models.